2018
DOI: 10.1021/acs.analchem.8b03547
|View full text |Cite
|
Sign up to set email alerts
|

Branch-Migration Based Fluorescent Probe for Highly Sensitive Detection of Mercury

Abstract: Detection of heavy metals is of great importance for food safety and environmental analysis. Among various heavy metal ions, mercury ion is one of the most prevalent species. The methods for detection of mercury were numerous, and the T-Hg-T based assay was promising due to its simplicity and compatibility. However, traditional T-Hg-T based methods mainly relied on multiple T-Hg-T to produce enough conformational changes for further detection, which greatly restrained the limit of detection. Hence, we establis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 38 publications
0
22
0
Order By: Relevance
“…Fluorescent sensors based on small molecules, in particular, have significant advantages such as their exquisite and noninvasive size, high sensitivity, selectivity, and fast response time. To date, numerous fluorescent Hg 2+ ( Chen, et al, 2015 ; Kim, et al, 2012 ) probes have been reported based on varieties of fluorophore like Rhodamine ( Bera, et al, 2014 ; Chang, et al, 2018 ; Su, et al, 2017 ; Tang, et al, 2017 ; Zhao, et al, 2010 ), BODIPY ( Hatai, et al, 2012 ; Lu, et al, 2009 ; Yoon, et al, 2005 ), Coumarin ( Sie, et al, 2017 ; Puthiyedath and Bahulayan, 2018 ), Schiff base ( Chen, et al, 2018 ; Duan, et al, 2019 ; Sarkar, et al, 2016 ; Wang, et al, 2018b ; Wang, et al, 2018d ; Zhang, et al, 2017 ), AIE luminophore ( Chen, et al, 2017 ; Selvaraj, et al, 2021 ; Wang, et al, 2018a ), Peptide-based benzoxazole unit ( Oliveira, et al, 2011 ; Oliveira, et al, 2013 ), etc. These probes were usually prepared either through the complexation with the multiple binding sites or through a chemical reaction with the proper functional group onto fluorescent molecules.…”
Section: Introductionmentioning
confidence: 99%
“…Fluorescent sensors based on small molecules, in particular, have significant advantages such as their exquisite and noninvasive size, high sensitivity, selectivity, and fast response time. To date, numerous fluorescent Hg 2+ ( Chen, et al, 2015 ; Kim, et al, 2012 ) probes have been reported based on varieties of fluorophore like Rhodamine ( Bera, et al, 2014 ; Chang, et al, 2018 ; Su, et al, 2017 ; Tang, et al, 2017 ; Zhao, et al, 2010 ), BODIPY ( Hatai, et al, 2012 ; Lu, et al, 2009 ; Yoon, et al, 2005 ), Coumarin ( Sie, et al, 2017 ; Puthiyedath and Bahulayan, 2018 ), Schiff base ( Chen, et al, 2018 ; Duan, et al, 2019 ; Sarkar, et al, 2016 ; Wang, et al, 2018b ; Wang, et al, 2018d ; Zhang, et al, 2017 ), AIE luminophore ( Chen, et al, 2017 ; Selvaraj, et al, 2021 ; Wang, et al, 2018a ), Peptide-based benzoxazole unit ( Oliveira, et al, 2011 ; Oliveira, et al, 2013 ), etc. These probes were usually prepared either through the complexation with the multiple binding sites or through a chemical reaction with the proper functional group onto fluorescent molecules.…”
Section: Introductionmentioning
confidence: 99%
“…7 Recently, using the target-induced branch migration of complementary DNA sequences, we developed a structureswitching aptamer beacon for mercury (Hg 2+ ) detection in a FRET manner. 8 Although these FABs showed great potential in environmental analysis, commercially available FABs for biological applications are still scarce. Generally, there are two main challenges limiting the commercialization of such FABs.…”
mentioning
confidence: 99%
“…A branch-migration based FAB reported in the previous work for Hg 2+ detection was selected as the model beacon to construct an integrated LPME-FAB system. 8 The principle of this FAB is also described (Scheme S1). In this design, the integrated aptamer beacon was included in the acceptor solution of FM-LPME.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Mercury ion (Hg 2+ ), one of the most hazardous pollutants, can accumulate in the human body through drinking water, thereby causing neural damage. , Currently, various techniques have been reported for Hg 2+ detection, such as atomic fluorescence spectrometry (AFS), coupled plasma mass spectrometry (ICPMS), fluorescence, , colorimetric methods, , and electrochemical techniques. , These innovative methods generally possess high selectivity and sensitivity. Among these methods, the electrochemical technique, with advantages of excellent sensitivity, simple instrumentation, relatively low cost, and rapid response time, has experienced soaring popularity in Hg 2+ assays. , Here an electrochemical biosensor based on a 3D DNB and electroactive 2D MOFs nanosheets was developed for ultrasensitive detection of Hg 2+ .…”
mentioning
confidence: 99%